Análisis bibliométrico de la literatura científica publicada en "Ciencia. Revista hispano-americana de ciencias puras y aplicadas" Ciencia, Spanish researchers, Exile, Hispano-America, Spanish civil War, Bibliometrics, Bibliometric analysis - Antonio Pulgarin; Cristina Carapeto; Jose M. Cobos (Information Research: An International Electronic Journal)
This paper reports the pilot stage of a Project whose objective is to analyse the scientific output of the journal “Ciencia” from its appearance (1940) until its closure (1974). The journal constituted the formal channel for the dissemination of science among Spanish researchers in exile in Hispano-America due to the Spanish civil War (1936-1939). The original articles published in three of the seven sections into which the journal was divided – Modern science (section I), Original communications (section II), and Applied science (section IV) – are studied, together with the bibliographical references contained in those articles. The number of articles analysed was 972, and of bibliographical references 14,184.